DISCHARGE SIMULATIONS WITH RAINFALL VARITIONS AND LAND COVER SCENARIOS (Case Study: Upper Citarum Watershed) - LUH DEVI AGUSTIANI - NIM: 12814009 , NI
The operation of the Saguling Reservoir depends on the water supply from the Citarum River. Water supply for the reservoir is affected by rainfall in the Upper Citarum watershed. Besides that, land cover also affected the flow in a watershed. This research conducted numerical simulations using Soil and Water Assessment Tools (SWAT) hydrological model to determine the discharge at the Nanjung Outlet which is the outlet of the Upper Citarum watershed and inlet of the Saguling Reservoir with rainfall variations and land cover change scenarios. Rainfall variations used in this research are upper extreme, normal, and lower extreme. Land cover used was land cover 1994 which represented watershed condition with many forest, land cover 2005 representing current conditions, and predicted land cover in 2025. This simulation used rainfall data which result from statistical correction bias on each grid of the Upper Citarum watershed from CHIRPS and observation rainfall data. The data is used as input SWAT hydrological model to produce Citarum Hulu watershed discharge based on rainfall variations and land cover change. Simulation in the December-January-February period (DJF) results that land cover change, especially forest cover decrease and settlement cover increase toward land cover 1994 cause increase in peak discharge and decrease in low discharge due increase in surface runoff dan decrease in base flow. Increase in discharge toward discharge with land cover 1994 dominant caused by surface runoff during high rainfall. However, decrease in discharge toward discharge with land cover 1994 dominant caused by baseflow at the previous day during low rainfall.